Computational Study on Association Rule Mining Using Microarray Data - Mohan Kumar, K; Devi, S (International Journal of Computer Sciences and Engineering, 2025)
Data mining is used to bring out the unknown information from known large data set. In data mining Association Rule Mining (ARM) is a technique which discovers the frequent relation between the patterns by using the terms support and confidence. Apriori, Partition, Border and Incremental algorithms are some of the algorithms in ARM. In this work microarray dataset for psychological disorders is extracted from GEO data base, applied Apriori algorithm, implemented using R tool and recognized the relationship between the diseases in psychological disorder.